Go cashless! Factors affecting the behavioural intention towards e-wallet among gen Z during the Covid-19 pandemic in Malaysia: a case study in Sabah, Malaysia - Tan, Yie Ling (2022)
The research is aimed to investigate the factors that affect the behavioral intention towards e-wallet among Gen Z during the Covid-19 pandemic in Sabah, Malaysia. The study examines the behavioral intention towards e-wallet by including independent variables of social influence, perceived ease of use, perceived usefulness, perceived privacy and security, and government support, mediator of attitude toward e-wallet with the aid of TAM theory. Target respondents that included in the research are generation Z in Sabah, Malaysia by collecting data with a total of 385 sets of survey questionnaires. SmartPLS 4 is used to assist in our data analysis along the research. Reliability test, discriminant validity, significance of variables, bootstrapping is applied in the data analysis. The results concluded that the attitude partially mediating the independent variables of perceived ease of use, perceived privacy and security and social influence on the behavioral intention towards e-wallet among generation Z in Sabah, Malaysia during the Covid-19 pandemic. Conversely, perceived usefulness and government support have a direct effect on the acceptance of e-wallet among generation Z in Sabah, Malaysia during the Covid-19 pandemic. Some limitations and suggestions are included in the study to provide a better idea for future researchers, application developers and government to enhance the adoption of e-wallet in Malaysia.